A text mining analysis of online reviews of Indian hotel employees. Issue 2 (3rd April 2021) - Chittiprolu, Vinay; Singh, Swati; Bellamkonda, Raja Shekhar; Vanka, Sita
ABSTRACT: Based on the premise of Market-focused Human Resource Management we propose that organizations should attend to employee voice. To this end, online reviews have emerged as a significant source of key information. We performed our analysis on (n = 2751) Glassdoor reviews of 22 hotel chains in India. We employed text mining tools to identify determinants of employee motivation and dissatisfaction. Organizational culture, career growth opportunities, and flexibility-motivated employees. Poor work–life balance, office politics, and high attrition rate de-incentivized employees. Further, the regression analysis of numerical ratings revealed that compensation and work–life balance are hygiene factors; career opportunities and cultural values emerged as dominant predictors of overall employee satisfaction. Practical, policy, and theoretical implications of these findings are discussed.